2010
DOI: 10.15666/aeer/0801_019038
|View full text |Cite
|
Sign up to set email alerts
|

Algal Indication of Pollution in the Low Er Jordan River, Israel

Abstract: Abstract. The Lower Jordan River is one of the most polluted in Israel. We used algal bio-indicators to monitor pollution levels in the dry and rainy seasons in order to assess a self-purification capacity of the aquatic ecosystem. We used 135 species of algae and cyanobacteria as indicators of pH, salinity, and organic pollution. The indices of saprobity (S and EPI), river pollution, RPI, and toxicity, BI testify to a greater anthropogenic impact in the lower section, partly owing to influx of pollutants with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…It has been shown that the composition of algal communities changes towards the predominance of species capable of heterotrophic nutrition under the conditions of toxic effect (Barinova et al, 2010a(Barinova et al, , 2010b(Barinova et al, , 2015. Such species are usually flagellate algae from the dinophyte Division.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the composition of algal communities changes towards the predominance of species capable of heterotrophic nutrition under the conditions of toxic effect (Barinova et al, 2010a(Barinova et al, , 2010b(Barinova et al, , 2015. Such species are usually flagellate algae from the dinophyte Division.…”
Section: Discussionmentioning
confidence: 99%
“…Alkalibiontes, which are tolerant to excessive alkalinity, were represented by 2 species (Figure 2a-f). Most of the rivers and streams in Turkey, Europe and nearby phytogeographic realms have an alkaline character (Barinova et al 2006a;Barinova, et al 2010b;Noga et al 2016;Sládeček, 1986). Indicators of salinity (79 species, 53.4%) were assigned to 4 ecological groups and arranged along the gradient of salinity.…”
Section: Resultsmentioning
confidence: 99%
“…and Phacus cudatus (Euglenophyta). Many species of the mentioned genus have standing-stream characteristics and wide saprobic tolerance, from oligo-saprobic to mesosaprobic (Barinova et al 2010a;2010b;2011a;Barinova, Nevo & Bragina, 2011b). In fact, most of the species in Table 2 are oligohalobious-indifferent and serve as the indicator species of these ecological …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated integral index of aquatic ecosystem sustainability (Aquatic Ecosystem State Index, WESI) is based on the water-quality classes (Barinova et al, 2006(Barinova et al, , 2010aBarinova, 2011;Barinova and Krassilov, 2012;Barinova and Sivaci, 2013) reflecting self-purification capacities for each of the sampling stations. If WESI is equal to or larger than 1, the photosynthetic level is positively correlated with the level of nitrate concentration.…”
Section: Bio-indication and Indices Calculationmentioning
confidence: 99%